2017
DOI: 10.3390/met7100395
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Incorporated Sn in Resynthesized Ni-Rich Cathode Materials on Their Lithium-Ion Battery Performance

Abstract: LiNi x Co y Mn z (NCM), one of the most promising candidates for high-capacity cathode materials in Li-ion batteries (LIBs), is synthesized with various amounts of Sn. Sn-incorporated NCM from the resynthesis of NMC in leach liquor containing Sn from spent LIBs is characterized by scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, particle strength tests, and electrochemical tests. Sn-incorporated NCM has a globular form, and the uniform dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Accordingly, the trace amount of impurities that are not fully eliminated from the leachate are incorporated during the co-precipitation for the direct regeneration of cathode active materials and affect the electrochemical performance of the resynthesized cathode active materials. In our previous study, the effects of impurity elements including iron, aluminum, tin, lithium, copper, and sodium were investigated individually at impurity levels [10][11][12][13][14][15][16]. It was reported that Li[Ni 1/3 Mn 1/3 Co 1/3 ]O 2 (NMC) containing trace amounts of Fe or Al via co-precipitation showed better LIB performance in terms of cyclability and rate capability compared to a pristine sample [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the trace amount of impurities that are not fully eliminated from the leachate are incorporated during the co-precipitation for the direct regeneration of cathode active materials and affect the electrochemical performance of the resynthesized cathode active materials. In our previous study, the effects of impurity elements including iron, aluminum, tin, lithium, copper, and sodium were investigated individually at impurity levels [10][11][12][13][14][15][16]. It was reported that Li[Ni 1/3 Mn 1/3 Co 1/3 ]O 2 (NMC) containing trace amounts of Fe or Al via co-precipitation showed better LIB performance in terms of cyclability and rate capability compared to a pristine sample [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of petroleum liquid catalyst [11], Sn-incorporated LiNi x Co y Mn z (NCM) [12], Ni nanosized powder [13] was investigated using leach liquor of a lithium ion battery (LIB). Joo et al [11] introduced a comprehensive recycling process, which included physical separation, leaching, solvent extraction and stripping, to prepare CMB (cobalt-manganese-bromide) and CMA (cobalt-manganese-acetate) liquid catalysts as petroleum liquid catalysts from the cathode materials of spent lithium ion batteries.…”
Section: Preparation Of Valuable Materials From Wastementioning
confidence: 99%
“…Joo et al [11] introduced a comprehensive recycling process, which included physical separation, leaching, solvent extraction and stripping, to prepare CMB (cobalt-manganese-bromide) and CMA (cobalt-manganese-acetate) liquid catalysts as petroleum liquid catalysts from the cathode materials of spent lithium ion batteries. Kang et al [12] investigated the effect of Sn impurity on the LIB performance of Ni-rich NCM, resynthesized from leach liquor of spent LIB by conducting analyses such as scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) mapping, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). Shin et al [13] investigated the fabrication of Ni nanosized powder from cathode active material, such as LiNiO 2 (LNO), as found in spent lithium ion batteries through a reduction with hydrazine monohydrate.…”
Section: Preparation Of Valuable Materials From Wastementioning
confidence: 99%
“…Among them, doping is an effective strategy to improve stability of layered structure because the dopant ions help suppression of the phase transition and the voltage fading. So far, lots of single dopants have been explored such as Al 10 , Ti 11 , Zr 12 , Mg 13 , Mo 14 , Na 15 , Sn 16 , B 17 , Fe 18 and Cr 19 to improve the electrochemical performance of layered cathode materials. Vanadium was also studied as one of the dopant by many researchers because vanadium can take various valence state, leading to the stability of the crystal and increase of Li-ion diffusion coefficient 2023 .…”
Section: Introductionmentioning
confidence: 99%